Upaya Meningkatkan Keterampilan Mengolah Informasi Siswa dalam Pembelajaran Sejarah melalui Strategi PQRST - Rany Amelia Hadiatiningsih; Yeni Kurniawati (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
This research is entitled “Application of the PQRST Strategy as an Effort to Improve Students’ Information Processing Skills in Learning History (Classroom Action Research in Class XI IPS 1 SMA PGRI 1 Bandung)”. Researcher found several indications that showed the information processing skills of class XI IPS 1 students were still very low. This research was conducted with the aim of describing the planning of implementing the PQRST strategy, describing the implementation of the PQRST strategy to improve students ‘information processing skills, providing an overview of improving students’ information processing skills in historical learning, and describing the efforts of researcher in overcoming obstacles encountered when implementing the PQRST strategy. There are three indicators of students’ information processing skills, namely skills in gathering information sources, selecting and managing information, and communicating information. The method which is used in this study is a classroom action research (CAR) method with a research design from Kemmis Tagart which is consisting of four stages, namely: planning, action, observation, and reflection. This improvement can be seen from the achievement of excellent scores on several indicators of information processing skills such as gathering information sources, selecting and managing information, and communicating information. Based on the results of the research, the application of the PQRST strategy can be a solution to improve students’ information processing skills in learning history in class XI IPS 1 SMA PGRI 1 Bandung.